Effect of San'ao decoction on aggravated asthma mice model induced by PM2.5 and TRPA1/TRPV1 expressions. (23rd May 2019) - Wang, Pengli; Liu, Hong; Fan, Xinsheng; Zhu, Zhenhua; Zhu, Yue
Abstract: Objective: San'ao decoction (SAD), a traditional Chinese prescription, is well-known in asthma treatment. In the current study, the protective role of SAD and its mechanism in aggravated asthma mice model via regulation of TRP channel were evaluated and explored. Methods: UPLC-QTOF-MS was used for analyzing the chemicals in SAD. The major chemical components in SAD were separated and detected under an optimized chromatographic and MS condition. 75 BALB/c mice were randomly divided into five groups: normal group, model group, dexamethasone group (0.75 mg kg −1 ), SAD-high dose group (1.8 g kg −1 ) and SAD-low dose group (0.9 g kg −1 ). A 42 days aggravated asthmatic model was established in mice induced by ovalbumin (OVA) plus PM2.5 (1.6 mg kg −1 ). After treated with corresponding medicine, peripheral blood and bronchoalveolar lavage fluid (BALF) from each group were assessed, airway responsiveness was determined, histopathological changes in lungs were detected, relevant cytokines and neurokines levels were measured, TRPA1 and TRPV1 mRNA and protein expressions in lung tissues were examined as well. Results: 21 signal peaks of the chemicals in SAD were identified with the method of UPLC-QTOF-MS. SAD, especially SAD-high dose exerted significant effects on OVA plus PM2.5 mice model in relieving lung injury score (P < 0.05), reducing eosinophil (EOS) count in blood (P < 0.05) and inflammatory cells ratio in BALF (P < 0.05, P < 0.01), decreasing RI value (P < 0.05) while increasing Cdyn value (P < 0.05), reducing IL-13, PGD2 and NGF levels in BALF (P < 0.01), as well as down-regulating TRPA1 and TRPV1 mRNA and protein expressions in lung tissues (P < 0.05, P < 0.01). Conclusion: SAD could improve pulmonary functions, relieve lung injury, as well as reduce IL-13, PGD2 and NGF levels of OVA plus PM2.5 aggravated asthma model in mice. The effect and mechanism of SAD might be related to the inhibition of TRPA1 and TRPV1 channels. Graphical abstract: Image 1